Russia needs the Subjective Philosophy - S. Z. Gontcharov (Образование и наука)
Based on the comparative analysis of different kinds of philosophic thinking, the paper reveals the advantages of subjective philosophy – the most adequate universal essentiality of socialized human being, opening the prospects for Russia as the creative society of cultural spontaneous activity. Objective principle of thinking is limited by the logic of outward definition. According to the above logic, people are regarded as tiny parts of social mechanism, the objects of manipulation. Separating action from spontaneous activity, object changes from self-alteration of human subject, executive functions from norm-creating ones brings about alienated practices and such social situation that makes individuals perceive their own existence as alien non- existence, or opposing existence.Subjectivity is a form of social activity regarding individuals and groups according to their ability in self-definition, self-organizing, self-control, norm-creating, as well as their actual rights and duties in social spheres of needs and objectives, and their feasible power over forces of nature and society. Subjective philosophy perceives the material production as the means for cultivating wholesome and spontaneously active individuals due to educational fundamentality and cultural prosperity. Accordingly, accumulation of capital turns into accumulation of culture and personal creativity growth. The results of the undertaken analysis and its conclusions can be implemented in developing creative anthropological bases for philosophy, pedagogy, psychology, economics, political science, as well as the relating discipline teaching.